Prevalence and Determinants of Sickness Absenteeism among Healthcare Workers in a Tertiary Hospital in Southwestern Nigeria - Ajayi, Paul O.; Olanrewaju, Temitope M.; Ipinnimo, Tope; Akinwumi, Adebowale F.; Esan, Deborah T.; Fakayode, Latifat A.; Adeyemi, Famous O. (International Journal of Occupational Safety and Health, 2024)
Introduction: Sickness absenteeism is a global problem that affects almost all forms of workers, especially healthcare workers. This study assessed the prevalence and determinants of sickness absenteeism among healthcare workers in a tertiary hospital in Southwest, Nigeria. Methods: An institutional-based, cross-sectional study was conducted among 360 healthcare workers in a Tertiary Hospital in Southwest, Nigeria from October to December 2022. A pre-tested interviewer-administered, semi-structured questionnaire was used to elicit information from the respondents who were selected using a stratified sampling technique. Bivariate analysis and binary logistic regression analysis were performed to identify the predictors of sickness absenteeism using SPSS version 25.0. The significance of associations was determined at p-value < 0.05. Results: The mean age ± SD of the respondents was 34 ± 7.15 years. The prevalence of sickness absenteeism among the health workers was 21.0%, while the causes of sickness absenteeism were malaria (51%), body pain (18%), and diarrhea (5%). Family obligation (AOR: 2.1, 95% CI: (1.20, 3.53), P=0.009) and the job type (AOR: 2.7, 95% CI: (1.05, 6.83), P=0.038) were the only predictors of sickness absenteeism. Conclusion: About one-fifth of the respondents had one spell of sickness keeping them away from work due to illnesses such as malaria, diarrhea, and body pain. Preventive interventions should be instituted by stakeholders based on the identified factors to reduce the prevalence of sickness absenteeism among these populations.